Circulating microRNA: Myocardium-derived prenatal biomarker of ventricular septal defects - Yang, Yiru; Yang, Hainan; Lian, Xihua; Yang, Shuping; Shen, Haolin; Wu, Shufen; Wang, Xiali; Lyu, Guorong (Frontiers in Genetics, 2022)
Background Recently, circulating microRNAs (miRNAs) from maternal blood and amniotic fluid have been used as biomarkers for ventricular septal defect (VSD) diagnosis. However, whether circulating miRNAs are associated with foetal myocardium remains unknown. Methods Dimethadione (DMO) induced a VSD rat model. The miRNA expression profiles of the myocardium, amniotic fluid and maternal serum were analysed. Differentially expressed microRNAs (DE-microRNAs) were verified by qRT–PCR. The target gene of miR-1-3p was confirmed by dual luciferase reporter assays. Expression of amniotic fluid-derived DE-microRNAs was verified in clinical samples. Results MiRNAs were differentially expressed in VSD foetal rats and might be involved in cardiomyocyte differentiation and apoptosis. MiR-1-3p, miR-1b and miR-293-5p were downregulated in the myocardium and upregulated in amniotic fluid/maternal serum. The expression of amniotic fluid-derived DE-microRNAs (miR-1-3p and miR-206) was confirmed in clinical samples. Dual luciferase reporter assays confirmed that miR-1-3p directly targeted SLC8A1/NCX1. Conclusions MiR-1-3p, miR-1b and miR-293-5p are downregulated in VSD myocardium and upregulated in circulation and may be released into circulation by cardiomyocytes. MiR-1-3p targets SLC8A1/NCX1 and participates in myocardial apoptosis. MiR-1-3p upregulation in circulation is a direct and powerful indicator of foetal VSD and is expected to serve as a prenatal VSD diagnostic marker.